Development and Evaluation of the SISTEM (Socioscientific Issues Science Literacy Evaluation and Measurement) to Improve Students' Science Literacy - Wulandari, Tri; Viyanti, Viyanti; Hasnunidah, Neni; Rosidin, Undang (International Journal of Education, Culture, and Society, 2025)
Low science literacy among Indonesian students, as evidenced by international assessments like PISA, underscores the urgent need to enhance their ability to connect scientific knowledge with societal issues. This challenge is exacerbated by a shortage of assessment tools that integrate scientific concepts with real-world phenomena, limiting students’ capacity to apply science in addressing social problems. This study aimed to develop a socioscientific issues (SSI)-based science literacy assessment tool targeting junior high school students on the topics of heat, thermal expansion, and temperature. Employing a Research and Development (R&D) approach following the 4-D model (Define, Design, Develop, Disseminate), the study began with a needs analysis involving 15 teachers and 200 students across nine schools in Lampung Province. Guided by these findings, an SSI-based assessment instrument was designed and subjected to expert validation of content, construct, and language. The tool was then pilot-tested on 25 seventh-grade students at MTs N 3 South Lampung. Pre- and post-test evaluations revealed a significant increase in science literacy scores, from an average of 42.79 to 79.42. N-gain analysis indicated moderate improvement (0.64), while Cohen’s d demonstrated a large effect size (2.70), confirming the tool’s efficacy. The study concludes that the SSI-based assessment effectively enhances students’ conceptual understanding and their ability to relate scientific principles to real-world contexts. It further recommends extending the tool’s application to other science topics and diverse educational settings.